Enhancing Teacher Performance Assessment in Educational Institutions: An Extreme Programming Approach - Denny Jean Cross Sihombing (Jurnal Info Sains : Informatika dan Sains, 2023)
Optimal education quality can be achieved when teachers provide quality and effective teaching. To measure and improve teacher performance, teacher performance appraisal is crucial. Considering the complexity of teachers' tasks, the importance of objective and data-driven teacher appraisals, and the existing problems in teacher appraisal systems, this research aims to investigate and develop a better teacher performance appraisal system to improve education quality in educational institutions. This research adopts the Extreme Programming (XP) approach as the application development method. XP is one agile method that focuses on collaboration, flexibility, and iterative development. The results showed that the application development has reached the user acceptance testing stage. About 85 percent of test participants in user acceptance testing, including teachers, principals, and administrative staff, felt that the app met their needs and could be used well. This research contributes to improving the quality of education in educational institutions by introducing a technology-based teacher performance appraisal application to improve the efficiency and objectivity of the appraisal. In addition, this research develops an understanding of the use of Extreme Programming in developing educational applications.